Toxicity of hemimethyl-substituted cucurbit[7]uril. (October 2017) - Yang, Xue; Zhao, Wenxuan; Wang, Ziyi; Huang, Ying; Lee, Simon M.Y.; Tao, Zhu; Wang, Ruibing
Abstract: Hemimethyl-substituted cucurbit[7]uril (HMeCB[7]), a derivative of cucurbit[7]uril (CB[7]) with nearly identical host−guest complexation properties to that of the parent, has significant potential in biomedical sciences due to its superior solubility in water. Its toxicity profile has been investigated in this work, including its developmental and organ-specific toxicities, with both in vivo zebrafish models and a relevant in vitro cellular model. These results demonstrated that HMeCB[7] has negligible developmental toxicity at concentrations up to 3.2 mM and very moderate cardiotoxicity and hepatotoxicity at concentrations of ≥0.8 mM, and is thus generally less toxic than the parent CB[7]. Our results suggest that HMeCB[7] may be a promising candidate of excipient in medicinal and pharmaceutical research fields. Highlights: Toxicity of hemimethyl-substituted cucurbit[7]uril (HMeCB[7]) was evaluated. HMeCB[7] exhibited negligible developmental toxicity and modest cardiotoxicity. HMeCB[7] showed liver toxicity at concentrations of 0.4–0.8 mM and above. The safety profile of HMeCB[7] is generally superior to that of the parent CB[7].